Inter-University Network for Healthy Aging, Latin America and the Caribbean (RIES-LAC): a university contribution to the Decade of Healthy Aging - Iván Palomoa; Margarita Murgieri; Rafael Pizarro-Mena; Diego Andrés Chavarro-Carvajald; María Fernanda Lopez; Jeanine Mongelos; Aldo Sgaravatti; Patrick Alexander Wachholz; Jorge Gamonal; Robinson Cuadros (Brazilian Society of Geriatrics and Gerontology, 2024)
None.